Intermediate Dynamic Compression and Decreased Posterior Tilt With Interlocked Pins in Femoral Neck Fixation in Synthetic Bone - Brattgjerd, Jan Egil (J Biomech Eng, 2021)
Fixation failure with resulting non-union is the key complication after femoral neck fixation. It can be avoided by permitting dynamic compression and reducing rotation and posterior tilt of the femoral head. To achieve this, a novel implant that features an interlocking plate with three hook-pins (The Hansson Pinloc(®) System) was developed from the original two hook-pins. Only an enhanced torsional fixation by the implant modification is reported. The purpose was to compare the biomechanical compressive and bending stability of the original and modified implant in femoral neck fixation. To analyze the contribution of both modified components, three individual pins were included, although not in regular use. Forty-eight synthetic femurs with mid-cervical wedge osteotomies were fixated by two pins or identical triangular pin patterns with or without the plate. Eight specimens of each group were loaded cyclically in compression with an inferior wedge to simulate stance and anteroposterior bending with a posterior wedge to imitate sitting down. The clinically relevant stability measurements were stiffness and deformation. Fissure formation defined failure. The novel implant improved bending stability by 30% increased stiffness, 44% reduced deformation, and less frequent posterior neck fissure formation (p < 0.001) while increased compressive stability was only evident with 25% reduced deformation and less frequent inferior neck fissures (p < 0.001). These impacts were mainly mediated by the third pin, while the plate prevented a lateral fissure in compression (p < 0.001). The clinical stability was improved by dynamic compression and decreased posterior tilt by implant modification.